Organizational citizenship behavior of IT professionals: lessons from Poland and Germany*. Issue 2 (3rd April 2019) - Kowal, Jolanta; Keplinger, Alicja; Mäkiö, Juho
ABSTRACT: The purpose of this research is to investigate the similarities and differences in Organizational Citizenship Behavior (OCB) of male and female information technology (IT) professionals in Poland and Germany, which represent a transition economy and a developed economy, respectively. We examined two dimensions of OCB: individually-oriented (OCBI) and organizationally-oriented (OCBO). We conducted an online survey among 282 Polish respondents and 80 German respondents, using a combination of random and snowball sampling. We observed both similarities and differences between Polish and German IT professionals. Overall, female subordinates evaluated their supervisors' OCB more positively than did male subordinates. In contrast, female supervisors evaluated their subordinates' OCB less positively than did male supervisors. Also, it was evident that in Germany employees value OCB more than those in Poland. In conclusion, our findings contribute to the stream of existing research on the relationship between gender, country and OCB in transition and developed economies in Europe.